ROUTLEDGE HANDBOOK OF PHILOSOPHY, POLITICS, AND ECONOMICS - Melenovsky, C. M. ([S.l.] : ROUTLEDGE, 2022)
This handbook advances the interdisciplinary field of Philosophy, Politics, and Economics (PPE) by identifying thirty-five topics of ongoing research. Instead of focusing on historically significant texts, it features experts talking about current debates. Individually, each chapter provides a resource for new research. Together, the chapters provide a thorough introduction to contemporary work in PPE, which makes it an ideal reader for a senior-year course. The handbook is organizedinto seven parts, each with its own introduction and five chapters: I. FrameworksII. Decision-MakingIII. Social StructuresIV. MarketsV. Economic SystemsVI. Distributive JusticeVII. Democracy The "Frameworks"part discusses common tools and perspectives in PPE, and the "Decision-making"section shows different approaches to the study of choice. From there,parts on "Social Structures," "Markets" and "Economic Systems" each use tools from the three PPE disciplines to study and distinguish parts of society. The next part explains dominant theories and challenges to the paradigm of "Distributive Justice." Finally, apart on "Democracy" offers five challenges to current democratic practice.
Keywords: Philosophy; Political science; Economics; POLITICAL SCIENCE / General